Analysis Factors Associated with Work Accidents Among House Construction Workers in Karang Ayu - Kiswanto, Risa Wahyu Putri; Reswari, Berlian Syiffa Ardana; Anakita, Cantika Salya Manikawening; Ayesha, Danish (Universitas Negeri Semarang, 2024)
Globally, work-related injuries are a significant public health and economic issue, with approximately 5-7% of all deaths in industrialized countries caused by work-related injuries. Each year, work accidents cause 350,000 deaths and 270 million non-fatal serious injuries. Due to its high burden of occupational hazards, the construction industry is more at risk than other industries. Compared with workers in different occupations, building construction workers are three to four times more likely to die and twice as likely to be injured than workers in other occupations. This study aims to analyze the factors associated with the incidence of work accidents among house construction workers in Karangayu, Semarang Barat. This study used descriptive qualitative methods, including observation, interviews, and questionnaires. The result of this study is that factors can cause work accidents, such as age, unsafe actions such as not using PPE properly, and worker knowledge, which leads to unsafe actions. Still, in this observation, there are driving factors behind workers' unsafe actions, one of which is the non-compliance of house construction workers in Karangayu, Semarang.